Search for a heavy higgs boson in multi-higgs doublet models - Abouelrous, Amir (My University, 2019)
A number of excesses (around 3σ) in the proton-proton collision data collected during Run 1 by the ATLAS and CMS experiments at the Large Hadron Collider point to the possibility of extensions to the Standard Model Higgs sector. In Run 2, the excesses are much stronger which conﬁrms the observed Run 1 excesses. Of particular importance are the excesses in the production of multiple-leptons. While present in Run 1 data, these have become very signiﬁcant in Run 2. We introduce the Madala hypothesis in order to explain the excessess observed in the data. This hypothesis postulates a heavy boson H (Madala boson) and a lighter scalar S which can decay into both dark matter and Standard Model particles. To accomodate the excesses in the data, the dominant decay channel of the heavy boson H is: H → Sh, where h is the Standard Model Higgs boson. In this project we study two models which have an extended Higgs sector as compared to the Standard Model. First, we study Left-Right Symmetric Models and analyze the Higgs spectrum. Flavor Changing Neutral Currents constrain the mediating heavy boson to be of O(TeV). We apply global and discrete symmetries to suppress Flavor Changing Neutral Currents and to constrain the mass of the heavy boson mediating them to O(GeV). Then we analyzed the mass spectrum of the neutral boson and place a lower limit on the mass of the heavy boson H. Our analysis of global and discrete symmetries in Left-Right Symmetric Models constrained the heavy boson H that mediate Flavor Changing Neutral Currents to O(TeV). We conclude that Left-Right Symmetric Models cannot accomodate the heavy boson H. The second model we study is the Two-Higgs Doublet Model Plus a Scalar Singlet. We will analyze the branching ratios of the heavy boson H and the Z gauge boson using the program N2HDECAY. Then we discuss the results in the framework of the Madala hypothesis. Finally, we study the mass spectrum of the neutral heavy boson in Two-Higgs Doublet Model Plus a Scalar Singlet and determine if we can ﬁt the heavy boson H in the model. The results obtained in this research indicate that these models could accomodate the Madala boson. Further studies are required to perform oﬀ-shell decays of the heavy boson H.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulﬁllment of the requirements for the degree of Master of Science. March 2019